2022
DOI: 10.1088/1475-7516/2022/09/005
|View full text |Cite
|
Sign up to set email alerts
|

A general study of decaying scalar dark matter: existing limits and projected radio signals at the SKA

Abstract: We consider a decaying scalar dark matter (DM) with mass m χ  in the range 10 GeV – 10 TeV and vary the branching ratios of all possible two-body SM final states (excluding and including νν̅)  in the range 0%-100% to derive constraints on the total decay width Γ using the data collected by several astrophysical and cosmological observations. We find that, Γ ≲ 10-26 - 10-27 s-1 (excluding νν̅)  and Γ ≲ 10-24 - 10-26 s-1 (including νν̅)  are allowed, depending on the values of m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…Such radio waves can be tested by radio telescopes like the Square Kilometer Array (SKA) radio telescope [91]. It is found that the DM decay width up to Γ DM ≳ 10 −30 s −1 is detectable at SKA assuming 100-hour observation time [92].…”
Section: Jcap05(2024)071mentioning
confidence: 99%
“…Such radio waves can be tested by radio telescopes like the Square Kilometer Array (SKA) radio telescope [91]. It is found that the DM decay width up to Γ DM ≳ 10 −30 s −1 is detectable at SKA assuming 100-hour observation time [92].…”
Section: Jcap05(2024)071mentioning
confidence: 99%
“…On raising ρ to 0.7 GeV cm −3 [70][71][72][73], the limits become stronger by a factor of eight. Following [27,74], we parameterize the AMS-02 measured positron flux spectrum as a polynomial function (f (α)) of energy and define the χ 2 as…”
Section: Jcap08(2023)071mentioning
confidence: 99%
“…For further details of the analysis methodology, see [27,74]. In obtaining the limits on σv , we assume a single-component WIMP accounts for the entire DM content.…”
Section: Constraints On Total Annihilation Cross-sectionmentioning
confidence: 99%
“…limit can be obtained by χ 2 ( σv 95 ) ≡ χ 2 bf + 2.71. This methodology has been widely used in literature [17,58,59].…”
mentioning
confidence: 99%